Assessing low-carbon energy technologies against sustainability and resilience criteria: results of a European experts survey. Issue 5 (28th May 2017) - Grafakos, Stelios; Flamos, Alexandros
Abstract : The aim of this article is the assessment of low-carbon energy technologies in Europe against a set of sustainability and resilience criteria. The assessment was based on a survey that was conducted among 40 European experts. Solar Photovoltaic was the technology that proved to achieve high performance against many criteria, whereas nuclear was assessed by the experts with relatively low performance against most of the criteria. Furthermore, it became evident that there is high degree of convergence between the experts, and therefore high degree of confidence, on specific aspects such as the high level of public resistance against Nuclear and the low stability of energy generation of wind onshore. The experts had major disagreements on the performance of carbon capture and storage (CCS) technologies against technological maturity and innovative ability criteria, which reveals a high degree of uncertainty on how CCS will be deployed in the future, pointing out a direction for future research.